Implementation of Standard Operating Procedures by Waitstaff in Food and beverage service Department at Kuta Beach Hotel - Giri, I Gede Dena Andana; Sumertha, I Ketut Eli; Suthanaya, Putu Bagus (LPPM Universitas Dhyana Pura, 2026)
Consistent SOP implementation by Waitstaff in hotel food and beverage service operations is a critical determinant of service quality and guest satisfaction. This study aims to analyze the implementation of Standard Operating Procedures (SOP) by Waitstaff in the Food and beverage service Department at Kuta Beach Hotel, identify the inhibiting factors, and describe the efforts undertaken to overcome these challenges. A qualitative descriptive method was used with data collected through direct observation using a SOP compliance checklist, semi-structured interviews with the F&B Supervisor, Captain, and Waitstaff, and documentation of official SOP documents and guest feedback during September–December 2025. The results show that Waitstaff at Kuta Beach Hotel have generally implemented the service SOP sequence covering pre-opening preparation, guest greeting and seating, order-taking, food and beverage serving, billing, and farewell. However, inconsistencies were found particularly in the greeting response time, order accuracy, and farewell procedures. The main inhibiting factors identified are insufficient training frequency, inconsistent supervisory oversight, low motivation among some staff during peak hours, and workload pressure during high-season. Mitigation efforts include daily briefings, periodic SOP refresher training, use of a structured observation checklist, and motivational coaching by the supervisor. This study concludes that SOP implementation effectiveness is directly linked to the quality of training, supervision, and staff motivation, and recommends a more systematic training schedule and supervisory monitoring system for the hotel.